Achievement of low-density lipoprotein cholesterol targets in Chinese patients with atherosclerotic cardiovascular disease after receiving statins and ezetimibe - Cheng, Yinchu; Dong, Shujie; Shen, Peng; Sun, Yexiang; Lin, Hongbo; Zhai, Suodi (Frontiers in Cardiovascular Medicine, 2022)
Background: The importance of low-density lipoprotein cholesterol (LDL-C) lowering to reduce ASCVD risk is strongly emphasized. If the LDL-C goals are not achieved with statin therapy, combination with ezetimibe is recommended. Studies revealed a substantial gap between obtained LDL-C levels and LDL-C target in ASCVD patients. However, little is known about the achievement of LDL-lowering treatment targets in ASCVD patients receiving ezetimibe in addition to statins. Methods: This was a retrospective cohort study based on EHR data from the regional health information system of Yinzhou, an eastern coastal area of China. ASCVD Patients stratified as very high risk, taking both statin and ezetimibe for lipid control, and had at least one lipid test after ezetimibe initiation were included between January 2013 and July 2020. Descriptive statistics were used to summarize the LDL-C values and target value (1.8 mmol/L according to the Chinese guideline, 1.4 mmol/L according to the European guideline) achievements. Multivariable logistic regression was used to explore the influencing factors of target achievement rate. Results: A total of 1727 patients were included. The median follow-up time was 15.0 months. Taking 1.8mmol/L as the target value, the achievement rates of LDL-C over the first 3 follow up years were 50.6%, 31.3% and 30.3%, respectively. Taking 1.4mmol/L as the target value, the achievement rates were 25.6%, 15.5% and 16.5%, respectively. Multivariable analysis suggested that male patients (OR=1.78, 95%CI: 1.27-2.49), combined use of atorvastatin or rosuvastatin with ezetimibe (vs other statins, OR=4.64, 95% CI: 1.83-11.76), better medication adherence (OR=1.03, 95% CI: 1.01-1.04) and smoking cessation (vs smoking, OR=2.26, 95% CI: 1.27-4.02) were associated with a higher achievement rate, while baseline LDL-C level (OR=0.48, 95% CI: 0.41-0.56) and treatment course of statin before ezetimibe (OR=0.93, 95% CI: 0.89-0.98) were negatively associated with achievement rate. Conclusion: Long-term follow-up data based on a Chinese regional database shows that in very high-risk ASCVD patients taking ezetimibe in addition to statins, achievement of LDL-lowering treatment targets is still low and far from satisfactory in real-world setting. More efforts are needed to achieve optimal LDL-C levels.